2018
DOI: 10.1016/j.snb.2017.07.155
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating chemical multisensory devices for real world applications: An in-depth comparison of quantitative machine learning approaches

Abstract: Chemical multisensor devices need calibration algorithms to estimate gas concentrations. Their possible adoption as indicative air quality measurements devices poses new challenges due to the need to operate in continuous monitoring modes in uncontrolled environments. Several issues, including slow dynamics, continue to affect their real world performances. At the same time, the need for estimating pollutant concentrations on board the devices, especially for wearables and IoT deployments, is becoming highly d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 34 publications
1
79
2
Order By: Relevance
“…In the majority of cases, these tested LCS consisted of electrochemical sensors. Only for NO 2 did we observe that supervised learning techniques (ANN, RF, SVM) performed slightly better than MLRs when looking at the R 2 of comparison tests in the field, except for SVR, which is in slight contradiction with other studies [101]. However, the number of records is much higher for MLR than for supervised learning techniques.…”
Section: Calibration Of Sensorscontrasting
confidence: 84%
See 1 more Smart Citation
“…In the majority of cases, these tested LCS consisted of electrochemical sensors. Only for NO 2 did we observe that supervised learning techniques (ANN, RF, SVM) performed slightly better than MLRs when looking at the R 2 of comparison tests in the field, except for SVR, which is in slight contradiction with other studies [101]. However, the number of records is much higher for MLR than for supervised learning techniques.…”
Section: Calibration Of Sensorscontrasting
confidence: 84%
“…The use of supervised learning techniques (ANN, RF, or SVR) either did not improve performance for CO or gave similar results as MLR for NO. This is in slight contradiction with other studies on the performance of supervised techniques [100,101]. In the majority of cases, these tested LCS consisted of electrochemical sensors.…”
Section: Calibration Of Sensorscontrasting
confidence: 77%
“…In addition, the study concluded that the performances of the low-cost sensors were significantly impacted by temperature and relative humidity (RH). Recurrent NN architectures were also tested for calibrating some gas sensors (De Vito et al, 2018;Esposito et al, 2016). The results showed that the dynamic approaches performed better than traditional static calibration approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever the sensor response has a linear behavior with respect to the reference data, multiple linear regression (MLR) [11], [12], [14], [19] is used for calibrating the sensors. Nevertheless, when the response is non-linear, models such as K-nearest neighbors (KNN) [19], [20], Gaussian processes [20] and more recently supportvector regression (SVR) [14], [15], [21], random forest (RF) [13], [14], [20] and artificial neural networks (ANN) [11], [15], [20] have been used to calibrate low-cost sensors. Most of these works are focused on studying and analyzing the quality of different commercial low-cost sensors and the performance of electro-chemical sensors.…”
Section: Related Workmentioning
confidence: 99%
“…For this reason, much research has focused on the interaction of environmental conditions such as temperature and relative humidity [3], [4], [7], [8], [9] or on the interactions of other pollutants [10], [11] with respect to one pollutant sensor. In addition, there is recently a greater interest in comparing and studying [11], [12], [13], [14], [15] how signal processing techniques behave for calibrating different air pollution lowcost sensors in IoT platforms. Many of these investigations focus on comparing what is the error obtained using several linear and non-linear machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%